Student eCoaches are successful Change Agents - Thomas Tribelhorn; Roman Suter; Sevgi Isaak (Forum Neue Medien in der Lehre Austria, 2021)
Cultivating a sustainable culture of experimentation in higher education is no easy task. This paper presents a promising approach for application at universities. Carefully selected senior students completed a four-month intensive programme to gain professional competencies in technology-enhanced teaching as well as coaching skills. These highly qualified eCoaches actively supported university teachers with realising innovative learning scenarios. This way, a system of reverse mentoring was implemented and the eCoaches became change agents. Innovation projects had to be submitted in order to apply for eCoach support. Evaluation revealed a high level of satisfaction among the project leaders, i. e. higher-education teachers, and in some cases they indicated their excitement about how much they had learned from their eCoach, in addition to developing an innovative scenario.